An assessment of redfish in NAFO division 3M based on beaked redfish (S. mentella and S. fasciatus) data - Ávila de Melo, A.; Alpoim, R.; Saborido-Rey, Fran (Northwest Atlantic Fisheries Organization, 1999)
54 páginas, 2 apéndices, 8 figuras, 13 tablas.-- Scientific Council Meeting The present assessment evaluates the status of the 3M beaked redfish stock, regarded as a management unit composed of two populations from two very similar species (Sebastes mentella and Sebastes fasciatus). Survey bottom biomass and survey female spawning biomass of Div. 3M beaked redfish were calculated based on the abundance at length from Canadian and EU bottom trawl surveys for the periods 1979-85 and 1988-98 respectively and on the 3M beaked redfish length weight relationship from 1989-1998 EU survey data. During the former period both bottom biomass and female spawning biomass of beaked redfish were stabilised, with female spawning bottom biomass averaging a 42% proportion of the bottom biomass. Bottom female spawning biomass declined throughout the most recent period and represented on average just 9% of the survey bottom biomass over the past five years. A Separable VPA analysis (Pope and Shepherd, 1982) for the most recent period of 1989-98 was conducted. A traditional VPA was finally performed using the separable generated F’s matrix, providing estimates of total and female stock biomass for 3M beaked redfish. A logistic surplus production model which does not use the equilibrium assumption (Praguer, 1994 and 1995) was applied using the 1959-98 catch estimates with the STATLANT commercial catch and effort data (1959-1993) as well as the EU bottom biomass (1988-1998). The results, as regards biomass and fishing mortality trends given by the Separable VPA and the ASPIC analysis are identical within the same order of magnitude. Both models pointed out that the 3M beaked redfish stock experienced a continuous decline till 1994 due to a sharp increase of fishing mortality that peak in 1990. Since 1995 fishing mortality declined rapidly, allowing the survival of above average year classes from the turn of the decade. Not being severely affected by the boom of the shrimp fishery on 1993 and 1994, the survival and growth of those ...